(untitled) (Bangladesh Journal of Botany, 2019)
For HMW-GS, a total of 16 different subunits and 30 allelic haplotypes were identified. The expression of HMW-GS ranged from 3 to 5 per genotype instead of 6 per genotype, revealing the phenomenon of gene silencing. The 2* was the most frequent subunit for Glu-A1 locus and was found in 52.45% lines. Eight subunits were identified for Glu-B1 locus. Five subunit pairs i.e. 6+8, 7+8, 7+9, 13+16 and 17+18 were present in the germplasm. Some single subunits i.e. 6, 7, 8 and 20 were also found. Subunit pair 17+18 was the most frequent with a partial frequency of 32.17%. For Glu-D1, four subunit pairs i.e. 2+12, 5+10, 2+11 and 5+11 were observed. The 5+10 was the most frequent subunit for Glu-D1 and was present in 65.03% lines. The 2+12 subunit pair was identified in 34.97% lines. For Glu3 loci 18 LMW subunits were identified. For Glu-A3, five subunits i.e. b, c, d, e and g were identified. Eight subunits i.e. b, c, d, f, g, h, i and j were identified for Glu-B3 locus. Four subunits i.e. a, b, c and l were identified for Glu-D3 locus.